Risk factors of Pneumocystis jeroveci pneumonia in patients with systemic lupus erythematosus - Ratchaya Lertnawapan (2018)
Pneumocystis jeroveci pneumonia (PCP) is an opportunistic infection which occurs mostly in the immune-deficiency host. Although PCP infected systemic lupus erythematosus (SLE) patient carries poor outcome, no standard guideline for prevention has been established. The aim of our study is to identify the risk factors which will indicate the PCP prophylaxis in SLE. This is a case control study. A search of Ramathibodi hospital's medical records between January 1994 and March 2004, demonstrates 15 cases of SLE with PCP infection. Clinical and laboratory data of these patients were compared to those of 60 matched patients suffering from SLE but no PCP infection. Compared to SLE without PCP, those with PCP infection have significantly higher activity index by MEX-SLEDAI (13.6 ± 5.83 vs. 6.73 ± 3.22) or more renal involvement (86 vs. 11.6%, P < 0.01), higher mean cumulative dose of steroid (49 ± 29 vs. 20 ± 8 mg/d, P < 0.01), but lower lymphocyte count (520 ± 226 vs. 1420 ± 382 cells/mm3, P < 0.01). Interestingly, in all cases, a marked reduction in lymphocyte count (710 ± 377 cells/mm3) is observed before the onset of PCP infection. The estimated CD4+ count is also found to be lower in the PCP group (156 ± 5 vs. 276 ± 8 cells/mm3). Our study revealed that PCP infected SLE patients had higher disease activity, higher dose of prednisolone treatment, more likelihood of renal involvement, and lower lymphocyte count as well as lower CD4+ count than those with no PCP infection. These data should be helpful in selecting SLE patients who need PCP prophylaxis. © 2008 Springer-Verlag.